Analyzing kindergarten's Interior Spaces for Enhancing Children's Creativity Erbil City as a Case Study - Shareef, Rawaz; Husein, Husein (Anbar Journal of Engineering Sciences, 2022)
The promotion and activation of creativity in children is extremely valuable due to their age growth. All types of environments, such as geographical, social, physical, and cultural environments, have a huge impact on children's development. Many studies have discussed the role of the environment in general in the creativity and development of children. However, the effect of the physical environment specifically seems to be disregarded. Nowadays children spend a lot of their time in kindergarten, thus the physical environment of kindergarten affects the children's development and creativity. It is noticed that at the kindergartens of Erbil city, the majority of the factors that contribute to creativity have been disregarded. The kindergartens are more of an academic institution than a place where children can be entertained or encouraged to be creative. In this study, qualitative and quantitative methodologies are applied to analyze the interior spaces of kindergartens in Erbil city. This paper seeks to create a content environment that encourages children to improve their abilities and potential skills. The found results prove that the physical environment factors are effective and significant in increasing children's creativity in kindergartens.